HEDONISTIC LIFESTYLE AS IDENTITY OF BANDA ACEH TEENAGE CELEBGRAMS (A STUDY ON THE IMPACT OF ACCESSING CELEBGRAM'S INTAGRAM ACCOUNTS - Anisah, Nur; Rizki, Ellyana; Sartika, Maini; Muharman, Nadia; Azman, Zakirah (ASPIKOM Jabodetabek Region, 2023)
This research is titled “Hedonic Lifestyle as Identity of Banda Aceh’s Teenage Celebgrams (An Explanative Study the Impact of Accessing Celebgram’s Instagram Accounts). This research aims to determine the cause of Banda Aceh’s teenage celebgrams to refer the hedonic lifestyle as an identity and explain the process of the hedonic lifestyle became the identity of Banda Aceh teenage celebgrams. This research used a qualitative explanative method. The data collection techniques used in this research are semi-structural interview, non participant observation and documentation. This research focus on hedonic lifestyle as identity of Banda Aceh’s teenage celebgrams in adolescence according to the Department of Health starting from 17 to 25 years old. This research used Social Learning theory, that explains Banda Aceh’s teenage celebgrams learns and observes on other celebgrams hedonic lifestyle then made it as a role model then imitate it. The results of this research shows that one of the causes Banda Aceh’s teenage celebgrams lives hedonic lifestyle is because they had hedonic role models too. The reward in the form of self-satisfaction and pleasure as well as a positive response from the virtual environment, makes a teenage celebgrams in Banda Aceh committed to living a hedonic lifestyle. The hedonist lifestyle of a Banda Aceh teenager as an identity is seen through activities, interests and opinions. In this research, the dominant source in influencing the creation of identity of the Banda Aceh’s teenage celebgrams is peers and idol figures (role model).